Shewanella oneidensis FabB: A β-ketoacyl-ACP Synthase That Works with C16:1-ACP - Luo, Qixia; Li, Meng; Fu, Huihui; Meng, Qiu; Gao, Haichun (Frontiers in Microbiology, 2016)
It is established that Escherichia coli β-ketoacyl-ACP synthase (KAS) I (encoded by EcfabB) is the primary, if not exclusive, factor for elongation of the cis-3-decenoyl-ACP (C10:1-ACP) but not effective with C16:1- or longer-chain-ACPs. To test the extent to which these features apply to KAS I proteins in other species, in this study, we examined the physiological role of FabB in Shewanella oneidensis, an excellent model for researching type II fatty acid synthetic (FAS) system and its regulation. We showed that the loss of either FabA (the enzyme that introduces double bond) or FabB, in the absence of DesA which desaturizes C16 and C18 to generate respective C16:1 and C18:1, leads to a UFA auxotroph. However, fatty acid profiles of membrane phospholipid of the fabA and fabB mutants are significantly different, suggesting that FabB participates in steps beyond elongation of C10:1-ACP. Further analyses demonstrated that S. oneidensis FabB differs from EcFabB in that (i) it is not the only enzyme capable of catalyzing elongation of the cis-3-decenoyl-ACP produced by FabA, (ii) it plays a critical role in elongation of C16:1- and longer-chain-ACPs, and (iii) its overproduction is detrimental.